2020
DOI: 10.1016/j.rbms.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Cross-border reproductive care in the USA: who comes, why do they come, what do they purchase?

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Author comparisons of data published by the Centers of Disease Control and Prevention (CDC) in their annual national summary reports ( CDC, 2019 ) point to increased utilization of ART despite <35% of all intended ART retrievals currently ending in a live birth. Not only are there low overall success rates, which vary considerably by the age of the oocytes used, but the more complicated ART procedures, such as in-vitro fertilization (IVF) and embryo cryopreservation, used in gestational surrogacy (which are often exactly those proposed as possible solutions to future infertility) are not often covered by health insurance and are prohibitively expensive for many in the USA, making them a privilege afforded to a niche, relatively wealthy, clientele ( Bell, 2014 , Briggs, 2017 , Conrad and Leiter, 2004 , Greil et al, 2011 , Jacobson, 2020 , Seifer et al, 2018 ).…”
Section: Us Surrogacy and Reproductive Timingmentioning
confidence: 99%
“…Author comparisons of data published by the Centers of Disease Control and Prevention (CDC) in their annual national summary reports ( CDC, 2019 ) point to increased utilization of ART despite <35% of all intended ART retrievals currently ending in a live birth. Not only are there low overall success rates, which vary considerably by the age of the oocytes used, but the more complicated ART procedures, such as in-vitro fertilization (IVF) and embryo cryopreservation, used in gestational surrogacy (which are often exactly those proposed as possible solutions to future infertility) are not often covered by health insurance and are prohibitively expensive for many in the USA, making them a privilege afforded to a niche, relatively wealthy, clientele ( Bell, 2014 , Briggs, 2017 , Conrad and Leiter, 2004 , Greil et al, 2011 , Jacobson, 2020 , Seifer et al, 2018 ).…”
Section: Us Surrogacy and Reproductive Timingmentioning
confidence: 99%
“…The authors identified narratives of surrogacy as empowering and liberating surrogate mothers and furthering reproductive rights. Due to the cost associated with US surrogacy arrangements, the neoliberal commercial US surrogacy market attracts a clientele of wealthy intended parents (Jacobson, 2020; Thompson, 2016). However, in a study of meaning-making practices at a surrogacy support website, Berend (2016) argues that economic, contractual and personal relationships are interconnected in surrogacy in the United States.…”
Section: Respectability and Discursive Representation Of Gender Equal...mentioning
confidence: 99%
“…The movement of people to take advantage of assisted procreation and surrogacy techniques from one country to another is often referred to as "reproductive tourism": Inhorn and Patrizio (2009) point out that since this expression evokes the fun of holidays, while the experience of people who do it is usually very expensive and stressful and faced due to "the desperate need of a child", it should be replaced with the notion of "reproductive exile" (Inhorn & Patrizio, 2009, p. 905). On the other hand, however, it must be considered that the intended parents do not move only as a last resort (for example, when in their country surrogacy is prohibited, or allowed only in certain circumstances in which they do not fall): the countries are also chosen based on economic and logistical considerations, on the quality of the country's medical infrastructure, on the simplicity of bureaucratic procedures, on the ease in bringing the child to their own country with a suitable birth certificate or passport, on the personalization and ethics of the medical procedures offered, on the guarantees obtainable from the contracts, and on considerations regarding the geographical and cultural proximity with the surrogates (Jacobson, 2020;Saravanan, 2018). At this point, it is also worth clarifying that it is not only the intended parents who move, but also the gametes, embryos, and in some cases even the surrogates, who move to another country during the whole process or only for the implantation of the embryos or childbirth (Corradi, 2019;Schurr, 2018).…”
Section: Laws and Marketsmentioning
confidence: 99%
“…There are several actors in surrogacy transactions: fertility clinics, surrogacy firms or brokers, surrogacy agencies, egg supply agencies, in some cases also embryo transfer facilitators and counsellors (Klein, 2018).Heterosexual couples generally rely on surrogacy when the woman cannot carry out a pregnancy due to medical conditions such as the absence of a uterus, congenital, or because it has been removed, when the woman suffers from fibroids, epilepsy, placenta accreta, or when she has previously had miscarriages (Guseva & Lokshin, 2019). The surrogate must be pharmacologically prepared to host the embryos (SAMA, 2012) and a pre-implantation genetic diagnosis (PGD) is often made to ensure that there are no genetic diseases in the embryos (Jacobson, 2020). If more embryos successfully attach to the womb than the number of children desired by the couple, the surrogate will be asked to undergo a selective reduction of the embryos (Danna, 2014;Forman, 2015).…”
mentioning
confidence: 99%